The new power elite - Gautney, Heather (Oxford University Press, 2023)
"A "remake" of C. Wright Mills' The Power Elite, this book charts patterns of elite domination amid paradigmatic changes in the structuring of U.S. social institutions and political life since the postwar period that lay bare the essentially corrupt and authoritarian nature of neoliberal capitalism and the power elites behind it. Driven by an inexhaustible pursuit of profits and wealth accumulation, power elites of the last half century conceived of and imposed a new form of global capitalism that has positioned the "free market" as an ultimate political and cultural authority. In the process, they have suppressed policies and rules, social movements, and political organizations that might impede profitability and exacted an unspeakable toll on human and planetary life. Similar to Mills, The New Power Elite elucidates the means through which today's elites accumulate wealth and power, including the subordination of military and governmental systems, media and culture, and labor, finance, and production to "market imperatives." It departs from Mills, however, in accounting for major transformations in the political geography of corporations and labor, the rise of finance capital, and role of U.S. imperialism in the structuring of global capitalism. And, unlike Mills, the book argues that while the American State, mass media, and cultural institutions can still operate as a sites of contestation, political, military, and cultural institutions today should not be considered as autonomous from market forces, as their principal function is to serve the interests of capital and operate on its behalf"--